Pengaruh Pengeluaran Pemerintah, Investasi, Angkatan Kerja, dan Inflasi Terhadap Produk Domestik Bruto (PDB) Indonesia Tahun 2015-2022 - Ayunda Dwi Putri; Fista Lindu Aprilia; Debi Safitri Gultom; Sanusi Ghazali Pane (Masyarakat Ekonomi Syariah Bogor, 2024)
This research focuses on the influence of government spending, investment, labor force, and inflation on Indonesia's gross domestic product (GDP) in 2015-2022. This research explains the influence of inflation, government spending, investment, labor force on Indonesia's Gross Domestic Product. This research uses quantitative research with the method used panel data regression analysis assisted by the analysis tool, namely eviews. The data collection techniques in this research are observation and literature study. The results of the research show that statistical tests from the results of hypothesis testing on government spending and investment have increased by 1%, apart from that the workforce does not have a significant influence on Gross Domestic Product (GDP), while increasing inflation will reduce Gross Domestic Product (GDP). This research concludes that the labor force, government spending and investment variables have a positive and significant effect on Gross Domestic Product (GDP), while inflation has a negative and significant effect on economic growth, with the coefficient of the inflation variable being negative. This means that an increase in the inflation rate will tend to reduce Indonesia's Gross Domestic Product (GDP).